1996
DOI: 10.1007/s002040050336
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective distribution of the teratogenic thalidomide analogue EM12 in the early embryo of marmoset monkey, Wistar rat and NMRI mouse

Abstract: Thalidomide administration during early gestation results in specific and dramatic limb defects in primates, but not in laboratory rodents such as the rat and mouse. The thalidomide analogue EM12 [2-(2,6-dioxopiperidine-3-yl)-phthalimidine] was used in the present study because this compound is metabolically more stable and teratogenically more potent than thalidomide in the monkey. We have administered the pure enantiomers, since we have previously shown that S-EM12 proved to be much more teratogenic in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…We were also interested to determine whether the thalidomide enantiomers (R and S) and those of its more potent analog EM12 differ in their effects on explanted limb buds as they do in monkey embryos (Merker et al, 1988;Heger et al, 1994;Schmahl et al, 1996). Our data show that whereas R-thalidomide and R-EM12 do cause some limb defects, the S version of each is considerably more potent (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…We were also interested to determine whether the thalidomide enantiomers (R and S) and those of its more potent analog EM12 differ in their effects on explanted limb buds as they do in monkey embryos (Merker et al, 1988;Heger et al, 1994;Schmahl et al, 1996). Our data show that whereas R-thalidomide and R-EM12 do cause some limb defects, the S version of each is considerably more potent (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Although specific reasons for increased ROS production in rabbits are unknown, thalidomide pharmacokinetics between sensitive and insensitive species demonstrates differences in embryonic regions of accumulation. Schmahl et al (1996) showed that in utero exposure to radioactively labeled EM12, a highly teratogenic thalidomide derivative, to thalidomide-sensitive marmosets resulted in the preferential accumulation in the limb of, compared with other embryonic regions. Moreover, preferential accumulation of EM12 in the limb was not evident in thalidomide-resistant species, the rat and mouse (Schmahl et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Schmahl et al (1996) showed that in utero exposure to radioactively labeled EM12, a highly teratogenic thalidomide derivative, to thalidomide-sensitive marmosets resulted in the preferential accumulation in the limb of, compared with other embryonic regions. Moreover, preferential accumulation of EM12 in the limb was not evident in thalidomide-resistant species, the rat and mouse (Schmahl et al, 1996). Specific pharmacokinetics of thalidomide in rat and rabbit embryos have not been identified as of yet, but may account for the increased susceptibility to thalidomideinduced oxidative stress in the rabbit LBC.…”
Section: Discussionmentioning
confidence: 99%
“…Racemic thalidomide (Contergan s , 2-(2,6-dioxo-3-piperidinyl)-1H-isoindole-1,3(2H)-dione) was introduced in 1956 as a sedative and antinausea drug especially in the first trimester of pregnancy. (S)-(À)-thalidomide has proven to have severe teratogenic effects in animal experiments [81]. Infants born to women who used thalidomide had a high incidence of deformities in their limbs [82].…”
Section: Drugsmentioning
confidence: 99%